Association Analysis of Polymorphisms in Inflammation-Related Genes with Non-Hodgkin Lymphoma Susceptibility - Giang, Nguyen Hoang; Ha, Nguyen Trong; Thi Xuan, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2024)
Non-Hodgkin's lymphoma (NHL) is a common hematological malignancy that develops in the lymphatic system. A20, CYLD, IFN-γ, JAK2, PI3KCA, and TP53 are known as inflammation-related genes in autoimmune diseases and cancers. In the end, 126 patients with NHL and 109 healthy individuals with well-characterized clinical profiles were enrolled. Twelve variants in the above genes were determined by the Kompetitive allele-specific PCR (KASP) assay. As a result, among genotyped 12 SNPs, the AG genotype of the rs280500 in the TYK2 gene showed significantly higher frequency in the patient group compared to healthy individuals (P=0.05). In addition, no significant differences in genotype frequencies of the other SNPs were found between the two groups. In conclusion, the rs280500 in the TYK2 gene was the risk variant for NHL susceptibility and additionally contributed to understanding the genetic basis of NHL.